Design and application of a four-channel transmit/receive surface coil for functional cardiac imaging at 7T - Dieringer, Matthias A.; Renz, Wolfgang; Lindel, Tomasz; Seifert, Frank; Frauenrath, Tobias; von Knobelsdorff-Brenkenhoff, Florian; Waiczies, Helmar; Hoffmann, Werner; Rieger, Jan; Pfeiffer, Harald; Ittermann, Bernd; Schulz-Menger, Jeanette; et al. (Journal of magnetic resonance imaging, 2011)
Purpose To design and evaluate a four‐channel cardiac transceiver coil array for functional cardiac imaging at 7T. Materials and Methods A four‐element cardiac transceiver surface coil array was developed with two rectangular loops mounted on an anterior former and two rectangular loops on a posterior former. specific absorption rate (SAR) simulations were performed and a B 1+ calibration method was applied prior to obtain 2D FLASH CINE (mSENSE, R = 2) images from nine healthy volunteers with a spatial resolution of up to 1 × 1 × 2.5 mm3. Results Tuning and matching was found to be better than 10 dB for all subjects. The decoupling (S21) was measured to be >18 dB between neighboring loops, >20 dB for opposite loops, and >30 dB for other loop combinations. SAR values were well within the limits provided by the IEC. Imaging provided clinically acceptable signal homogeneity with an excellent blood‐myocardium contrast applying the B 1+ calibration approach. Conclusion A four‐channel cardiac transceiver coil array for 7T was built, allowing for cardiac imaging with clinically acceptable signal homogeneity and an excellent blood‐myocardium contrast. Minor anatomic structures, such as pericardium, mitral, and tricuspid valves and their apparatus, as well as trabeculae, were accurately delineated. J. Magn. Reson. Imaging 2011;. © 2011 Wiley‐Liss, Inc.